A Study on the Impact of Chamber Size, Configuration, Environmental Factors and Maximum Power Point Tracking (MPPT) Integration on Microbial Fuel Cell Voltage - Siti Kudnie, Sahari; Nashley Ursula, Mundi Ujai; Thommy, Thomas; Ibrahim, Yakub; Marini, Sawawi; Lilik, Hasanah; Abdul Rahman, Kram; Zaidi, Embong; Kasumawati, Lias; Annie, Joseph; Kho, Lee Chin; Sharifah Masniah, Wan Masra (Universiti Putra Malaysia Press, 2025)
The study examines the effect of chamber size, Microbial Fuel Cell (MFC) arrangement, environmental conditions on voltage production, and the influence of connecting Power Management System (PMS) with MFC. A 6-unit single-chamber MFC device was built using soil as a catalyst and coconut leaves as a substrate. It was then connected to a PMS. The study showed that a 350 ml MFC unit arranged in series produced a greater voltage of 457 mV compared to a 700 ml container. The smaller chamber was connected in series and integrated with a PMS consisting of a charge pump, DC-DC boost converter, and Maximum Power Point Tracking (MPPT), which led to a maximum stable voltage of 10.56 V. It highlights the possibility of increasing voltage consistently by using smaller MFC chambers, dirt as a catalyst, coconut leaves as a substrate, and aluminum as an electrode, together with a thorough PMS setup.